Inflammatory and healing environment in synovial fluid after anterior cruciate ligament reconstruction: Granulocytes and endogenous opioids as new targets of postoperative pain - Hiroki Katagiri; Kaori Nakamura; Takeshi Muneta; Toshifumi Watanabe; Kazumasa Miyatake; Ichiro Sekiya; Hideyuki Koga; Kunikazu Tsuji (Biochemistry and Biophysics Reports, 2021)
Background: Biological processes after anterior cruciate ligament reconstruction (ACLR) is crucial for recovery. However, alterations in the of synovial fluid cell population during the acute phase following ACLR and the relationship between these cells and postoperative pain is unclear. The goal of this study was to reveal alterations in synovial fluid cell population during the acute phase following ACLR and relationship between postoperative pain and proportion of synovial fluid cells. Methods: Synovial fluids were obtained from all patients (n = 50) before surgery and from patients who showed hydrarthrosis at days 4 (n = 25), and 21 (n = 42) post-surgery. The cell population was analyzed by flow cytometry. IL1β, IL8, and met-enkephalin in synovial fluid were quantitated by enzyme-linked immunosorbent assay. Patients answered numerical rating scale (NRS) questionnaire at 4 days and approximately 4 weeks postoperatively. Results: The granulocyte population was significantly higher at 4 days after surgery than at any other time points. The population of macrophages was 3.2 times and 7.7 times as high as at surgery on days 4 and 21, respectively. T cell population was significantly higher 21 days after surgery compared to 4 days after surgery. All NRS 4 weeks after surgery showed a significant negative correlation with the granulocyte population in synovial fluid 4 days after surgery. Granulocyte population in synovial fluid significantly correlated with the levels of IL1β and IL8. Postoperative pain at rest tended to decrease with an increase in met-enkephalin concentration 4 days after ACLR. Conclusions: Synovial fluid after ACLR had an inflammatory environment at early time points and a healing environment in the subsequent phase about concerning to the cellular composition. A proportion of synovial fluid cells and endogenous opioids affected postoperative pain.